O PAPEL DA EDUCAÇÃO PARA MULHERES EM SITUAÇÃO DE VULNERABILIDADE SOCIAL - Fiuza, Debora Rickli (2016)
This dissertation aimed to reflect on the role of education for women in situation of social vulnerability. The study was conducted with seven women, beneficiaries of the Brazilian income transfer program Bolsa Família in the city of Pitanga, state of Paraná. The research was supported by concepts that led the reflections, problematized some questions and theoretically justified the writing, being them Poverty, Human Rights, Gender and Education. The theoretical framework for the discussion of these concepts derived from authors such as Paulo Freire (1981; 1987; 1989), Boaventura de Souza Santos (2013, Joan Scott (2003), Pierre Bourdieu (1975, 1996), Costa (2005), among others. To implement the research and achieve the objective of this study it was used as methodological approach the method of Oral History, conducting interviews with the women, interviews those which were later transformed into narratives. From these narratives the analysis was organized into three chapters. The first chapter refers to the understanding of education as a condition of release, particularly from oppressive practices and relations. The reports made on the decision to return to study, the early literacy process and the wish to learn to read and write were articulated with the theoretical basis of the concepts of education, reproduction and liberation. The second chapter includes education as a necessary condition to face poverty. Thus, it problematized the concept of poverty with the understanding of public policies, social and human rights, emphasizing the mechanisms developed by the Ministério do Desenvolvimento Social e Combate à Fome (Department of Social Development and Fight Against Starvation) - Department of Combat and Fight Against Poverty. This chapter also discussed education as a way of empowering women and the changes brought about from the study. The third chapter seeks to discuss the gender relations involved in the educational processes. The reports presented express meanings, difficulties and barriers to the access to education which are involved in contexts of extreme poverty, supported by the condition of being a woman. Thus, the relationship between gender, education and poverty status intertwine in the discourses and denounce for these multiple determinations that conditioned and favored the removal from educational processes. From the tensions seized this work searched to build a research interrelated to reality. The woman in social vulnerability constituted of a significant theme for the relationship between knowledge and sociocultural practices, guided through critical looks in relation to the conditions produced and reproduced in the community settings. In this sense, it is considered an important contribution to the studies and interdisciplinary researches in the Community Development.